Relación entre la dieta y los niveles de colesterol total de los miembros de la asociación de exalumnos Ramiristas de ambos sexos del distrito de Moche, en abril del 2016 - Calvanapón Mendoza, Silvia Yenny (2016)
The relationship between diet and levels of total cholesterol using type simple, prospective and cross-sectional descriptive research, with a sample size of 48 members of the association ramiristas former students of both sexes, who participated voluntarily determined, is he used the enzymatic method according to Trinder. The results were validated in frequency distribution tables and Chi Square test with significance level α = 5%. Regarding cholesterol levels found that 37.5% had optimal level, 33.3% higher limit and 29.2% high level, moreover no statistical significance was found in confronting the serum cholesterol levels with sex (p = 0.55), age (p = 0.15), the female population which had higher cholesterol levels compared to men. Finally higher prevalence of high cholesterol (50%) in people who eat bread three days a week, just as those who consume noodles was found, being 50% also for this. Regarding meat who eat fish three times a week have 64.3% prevalence in presenting high cholesterol; those who consume red meat once a week, 78.6% and white meat, daily consumption is 71.4% of producing increased total cholesterol. In milk, drinking milk every day or even once a week leads to a 14.3% prevalence of high cholesterol, 50% for consumption once a week in cheese; 71.4% in the case of butter to be consumed once a week and 21.4% prevalence of high cholesterol by eating yogurt 3 times a week. The consumption of vegetables three times a week gives a percentage of 57.1% of presenting high cholesterol levels. It showed that daily consumption of fruits and vegetables produced 66.7% of desirable total cholesterol. Consumption of sausages once a week has a prevalence of 64.3% in presenting high cholesterol. Coffee consumed three days a week, even one day a week leads to a 28.6% risk of producing a high cholesterol